2022
DOI: 10.1021/acs.jafc.1c06000
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lotus Seed Resistant Starch on Lactic Acid Conversion to Butyric Acid Fermented by Rat Fecal Microbiota

Abstract: The aim was to investigate the effect of lotus seed resistant starch (LRS) on lactic acid (LA) conversion to butyric acid (BA) fermented by rat fecal microbiota to construct an acetyl CoA pathway. According to growth curves, the microbiota compositions at 10 and 36 h were further analyzed. The microbiota in the LRS group had higher richness and diversity compared to glucose (GLU) and high amylose maize starch (HAMS). Moreover, LRS and isotope LA promoted the growth of Lactobacillus and Bif idobacterium, promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It should be noted that this order was assigned only considering the RS content values itself. However, chemical characteristics of this type of RSs could increase their potential health benefits, in terms of SCFAs released and absorbed in the colon and the potential benefit on the growth of the probiotic microbiota [ 36 , 66 , 67 ]. For this reason, more studies are required to clearly establish the health promotion of this type of pasta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that this order was assigned only considering the RS content values itself. However, chemical characteristics of this type of RSs could increase their potential health benefits, in terms of SCFAs released and absorbed in the colon and the potential benefit on the growth of the probiotic microbiota [ 36 , 66 , 67 ]. For this reason, more studies are required to clearly establish the health promotion of this type of pasta.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, An [ 26 ] observed an opposite trend, which was attributed to the fact that oxidation hydrolytically degraded amylopectin and amylose (specifically in the amorphous regions of starch – amylose), thus facilitating the action of α-amylase. Likewise, the chemical modification of starch via organocatalytic esterification reaction using short-chain fatty acid (SCFA) precursors such as sodium butyrate (C 4 H 7 NaO 2 —NaBu) has been little studied in order to (1) increase the RS content [ 27 , 28 , 29 ], (2) raise the beneficial effect they cause on colon health [ 30 , 31 , 32 , 33 ], (3) regulate cholesterol in the blood [ 34 ], (4) modulate oxidative stress of colonic mucosa [ 35 ] and (5) enhance the growth of the colonic probiotic microbiota [ 36 , 37 , 38 , 39 , 40 , 41 ]. Additionally, the use of NaBu as a precursor of Bu to be grafted (esterified) onto the starch structure with the aim of obtaining REx-processed butyrylated starches has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…utilizing unmodified tapioca starch for a feeding period of 180-d observed the variation in cecal aerobic microflora with elevation of lactobacilli , while rats feeding with hydroxypropyl starch resulted in complete reduction of streptococci [ 36 ]. Previous research also showed that taking RS containing food also increase the proportion of microbes like lactobacillus and bifidobacteria in rats [ 31 , 37 ]. Whereas, Sáez-Orviz et al has also been confirmed that starch granules get penetrated in the probiotic bacterial cell and the bacteria degraded the starch granules analysed under by electron microscope [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contents of SCFAs were determined using a high-performance liquid chromatograph (HPLC) (Agilent 1200; Agilent Technologies Inc.) by the method reported by Zhiyun Wang. 24 First, 100 mg sample was acidified with aqueous sulfuric acid (0.12 mL, 2.5 mM). Volatile fatty acids were extracted by vibration centrifugation (5 000 rpm, 10 min).…”
Section: Methodsmentioning
confidence: 99%
“…In this work, 16S rRNA sequencing was performed according to the methods described by Zhiyun Wang. 24 Microbial community genomic DNA was extracted from fecal samples using the E.Z.N.A.® soil DNA Kit (Omega Bio-tek, Norcross, GA, U.S.) according to the manufacturer's instructions. The DNA extract was checked on 1% agarose gel, and the DNA concentration and purity were determined using a NanoDrop 2000 UV-vis spectrophotometer (Thermo Scientific, Wilmington, USA).…”
Section: Methodsmentioning
confidence: 99%